Ag, Ti dual-cation substitution in Cu2ZnSn(S, Se)4 induced growth promotion and defect suppression for high-efficiency solar cells. Issue 42 (19th October 2022) - Chen, Xing-Ye; Ishaq, Muhammad; Ahmad, Nafees; Tang, Rong; Zheng, Zhuang-Hao; Hu, Ju-Guang; Su, Zheng-Hua; Fan, Ping; Liang, Guang-Xing; Chen, Shuo
Abstract : A dual-cation-substituted Cu2 ZnSn(S, Se)4 involving Ag and Ti to separately occupy partial Cu and Sn is developed. Such a new strategy can simultaneously promote crystal growth and suppress detrimental defects, leading to a high efficiency of 12.73%. Abstract : The existence of various detrimental defects inside the absorber layer is a major obstacle limiting the performance of kesterite Cu2 ZnSn(S, Se)4 (CZTSSe) thin-film solar cells. Cationic substitution is a viable strategy for overcoming this challenge and has drawn tremendous research attention. In this work, a dual-cation substituted CZTSSe involving Ag and Ti to separately occupy partial Cu and Sn lattice sites is proposed. Under 6% Ag and 1% Ti dual-cation substitution, the champion CZTSSe device delivers a highly interesting efficiency of 12.73%, accompanied by an outstanding V OC of 530 mV. Further investigation demonstrates that Ag introduction can improve the density and crystallinity of CZTSSe thin films while decreasing the concentration of CuZn acceptor defects. Further Ti substitution can effectively eliminate fine grains and reduce the defect density of CuSn and [2CuZn + SnZn ] defects, as well as the core level defects. This work explores the synergistic effect of Ag, Ti dual-cation substitution in CZTSSe solar cells for the first time, and the clarified device performance improvement mechanism opens up promising possibilities for the bright development of CZTSSe thin-film photovoltaic technology.